Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru - Tohamba, Citra Prasiska Puspita; Risnajayanti; Asniati; Sagitayana, Elma; Edwar, Harisa (Jurusan Bahasa Inggris, 2024)
This research aims to describe the principal's leadership in improving teacher performance at An Nasar Kindergarten, Kendari City, fostering teaching discipline in improving teacher performance, supporting and inhibiting factors for teacher performance. This research used a qualitative approach with research subjects involving 3 people, namely: the school principal and teachers at An Nasar Kindergarten. For research data collection techniques using interview and observation techniques with data analysis techniques, namely reducing data, presenting data, verifying data and drawing conclusions. The results of this research show several important findings regarding the principal's leadership in improving teacher performance at An Nasar Kindergarten. First, the principal's leadership is effective in fostering teacher discipline through enforcing existing rules, as well as good teacher performance in preparing learning plans. Second, support from the school principal, including the provision of IT-based infrastructure such as: laptops, infocus, and curriculum guidebooks, is a supporting factor in learning. However, this research also identified the main obstacle in the form of inadequate learning media. However, this problem can be overcome with the competence of teachers at An Nasar Kindergarten.